2006
DOI: 10.1159/000089466
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Oral Iron Prophylaxis in Pregnancy – Myth or Reality?

Abstract: Background: It is a common belief among women that iron compounds have unpleasant gastrointestinal side effects. Objective: To assess the gastrointestinal side effects of iron prophylaxis in pregnancy. Methods: A randomized, double-blind study comprising 404 healthy pregnant women allocated to four groups taking ferrous iron supplement (as fumarate) in doses of 20 (n = 99), 40 (n = 100), 60 (n = 102) and 80 mg (n = 103) daily from 18 weeks of gestation to delivery. Iron supplement was predominantly taken at be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…These side-effects are dose dependent and become overt at ferrous iron doses above 100-180 mg/day. However, placebo controlled studies in pregnant women have shown that ferrous iron doses of 105 mg/day has a side effect profile, which is not significantly different from placebo [47,48]. The slow release iron formulas Ferro Duretter, IberetFolic and ferrous sulphate with mucoproteose (Tardyferon) have fewer gastrointestinal side-effects (nausea, epigastric pain, constipation) than fast release formulas [45,49,50].…”
Section: Iron Formulas: Fast and Slow Release Formulasmentioning
confidence: 99%
“…These side-effects are dose dependent and become overt at ferrous iron doses above 100-180 mg/day. However, placebo controlled studies in pregnant women have shown that ferrous iron doses of 105 mg/day has a side effect profile, which is not significantly different from placebo [47,48]. The slow release iron formulas Ferro Duretter, IberetFolic and ferrous sulphate with mucoproteose (Tardyferon) have fewer gastrointestinal side-effects (nausea, epigastric pain, constipation) than fast release formulas [45,49,50].…”
Section: Iron Formulas: Fast and Slow Release Formulasmentioning
confidence: 99%
“…33,34,39 The presence of side effects appear to impact upon the compliance with oral iron supplementation or as suggested by Melamed et al, 23 the woman's perceptions that the symptoms are related to the iron supplementation. It is accepted that oral iron supplements do cause gastrointestinal side effects, 1,16,21,22,37,38 many women appear to react to these perceived unacceptable side effects by ceasing their iron altogether without informing their healthcare professional. This reinforces the need for healthcare professionals to assess compliance to oral iron supplementation at every antenatal visit, as many side effects could be reduced to acceptable levels or resolved with changes to timing, dosage, brand or other measures including simple modifications to diet to counter side effects such as constipation.…”
Section: Group (No In Group) Mean Standard Deviationmentioning
confidence: 99%
“…3,9,10,12,[14][15][16] Gastro-intestinal side effects are frequently cited as a causative factor in reduced compliance to oral iron supplementation in pregnancy. 17,[19][20][21][22][23][24] However studies suggest that education, communication, social and cultural determinants also play a role in lack of motivation to comply with treatment. 7,17,19,25 This is compounded by a lack of recognition of the importance of preventing and treating iron deficiency anaemia, congruence of the symptoms of anaemia with advancing pregnancy and the use of natural or traditional remedies.…”
Section: Introductionmentioning
confidence: 99%
“…Les effets secondaires digestifs peuvent concerner jusqu'à 25 % des patientes recevant une supplémentation systéma-tique et sont d'autant plus fréquents que la dose en fer administrée est élevée (supérieure à 60 mg par jour) [26]. Une étude randomisée danoise trouvait, cependant, des taux similaires de troubles digestifs lorsque la supplémen-tation était comprise entre 20 à 80 mg par jour [28].…”
Section: Risques De La Supplémentation En Ferunclassified